Una aplicación de los modelos ARIMA en la predicción de la mortalidad por ataque con arma de fuego y explosivos para la ciudad de Medellín, de 1997 al año 2000 (1999)
ABSTRACT: This articule shows some theoretical elements and a application of the Arima modelation technique for the prediction of epidemiological events. This application was made througn a time series analysis to predict the mortality due to fireman injuries based on the information obtained in Medellín during 1987-1996.